A fast gas-mixing system for breath-to-breath respiratory control studies. - Robbins, P; Swanson, G; Micco, A; Schubert, W (1982)
A computer-controlled gas-mixing system that manipulates inspired CO2 and O2 on a breath-to-breath basis has been developed. The system uses pairs of solenoid valves, one pair for each gas. These valves can either be fully shut when a low voltage is applied, or fully open when a high voltage is applied. The valves cycle open and shut every 1/12 s. A circuit converts signals from the computer, which dictates the flows of the gases, into a special form for driving the valve pairs. These signals determine the percentage of time within the 1/12-s cycle each valve spends in a open state and the percentage of time it spends shut, which, in effect, set the average flows of the various gases to the mixing chamber. The delay for response of the system to commanded CO2 or O2 changes is less than 200 ms. The system has application for the manipulation of inspired gas fractions so as to achieve desired end-tidal forcing functions.